Overexpression of LINC00261 inhibits non–small cell lung cancer cells progression by interacting with miR‐522‐3p and suppressing Wnt signaling. Issue 10 (12th June 2019) - Shi, Jingli; Ma, Huimin; Wang, Huaixi; Zhu, Weiyan; Jiang, Shuting; Dou, Rui; Yan, Beizhan
Abstract: Long noncoding RNA LINC00261 has been experimentally validated to function as a tumor suppressor in several cancers, but its pathological role and functional mechanism in non–small cell lung cancer (NSCLC) are largely unclear. In this study, LINC00261 was delineated in NSCLC to be significantly downregulated in cancer tissues compared with corresponding adjacent normal tissues. Low expression of LINC00261 predicted worse survival for patients with NSCLC. Overexpression of LINC00261 in NSCLC cell lines inhibited cell proliferation and invasion, meanwhile promoted apoptosis. Subcellular fractionation assay showed that LINC00261 existed mainly in the cytoplasm of NSCLC A549 cells and luciferase assay validated its direct interaction with miR‐522‐3p. Overexpression of miR‐522‐3p significantly ameliorated suppressive effects of LINC00261 on proliferation and invasion of NSCLC cells. Besides, miR‐522‐3p was found to be able to directly combine with the 3′‐untranslated region of SFRP2, which was generally regarded as a suppressor of Wnt signaling. Further quantitative reverse transcription polymerase chain reaction and Western blot experiments showed that LINC00261 upregulation potentiated the expression of SFRP2 and inhibited Wnt signaling pathway, which could both be reversely modulated by miR‐522‐3p. Taken together, our study demonstrated that LINC00261 suppressed NSCLC cells progression via sponging miR‐522‐3p and inhibiting Wnt signaling. These results supported us to better understand the pathogenic mechanism of NSCLC and revealed a potential molecular target for this fatal disease. Abstract : Overexpression of LINC00261 in non–small cell lung cancer (NSCLC) cell lines inhibited cell proliferation, invasion, and promoted cells apoptosis. Overexpression of miR‐522‐3p significantly ameliorated the suppressive effects of LINC00261 on NSCLC cells proliferation and invasion. LINC00261 upregulation potentiated the expression of SFRP2 and inhibited Wnt signaling pathway, which could both be modulated by miR‐522‐3p.